Polacy i Kozacy w opowieści Gogola Taras Bulba - Kriwonos, Władysław (Przegląd Rusycystyczny, 2006)
POLES AND COSSACKES IN GOGOL’S TALE TARAS BULBA Summary In the present paper the symbolical meanings and special features of the image of Poles and Cos-sackes in Gogol’s tale Taras Bulba are considered. The analysis of this problem is very important for understanding of the author’s concept. Semantics of motives playing a key role in the description of Poles and Cossackes is found out. The material of Slavic national religious beliefs important for study of the principles of mythologization of the image is involved. As a result of the analysis new fashion of the important aspects of the semantic contents of the Gogol’s story are interpreted. POLACY I KOZACY W OPOWIEŚCI GOGOLA TARAS BULBA Streszczenie Artykuł podejmuje analizę symbolicznych znaczeń obrazu Polaków i Kozaków w opowieści Nikołaja Gogola Taras Bulba. Kluczową rolę odgrywa tu semantyka poszczególnych motywów poświęconych opisowi Polaków i Kozaków przez Gogola. Wśród nich znajduje się problematyka związana z religiami wyznawanymi przez poszczególne słowiańskie narody. Rezultatem analizy jest nowa interpretacja najważniejszych aspektów semantyki opowieści Gogola.